Hexacoordinated mononuclear Ag(I) complex crystal material, preparation method, loading material and device

By preparing a six-coordinated single-core Ag(I) complex crystal material, the problem of difficulty in separation between ethylene and ethane is solved, and an efficient and energy-saving gas separation effect is achieved. The material has good stability and selective adsorption properties.

CN119751341APending Publication Date: 2025-04-04SUZHOU JINHONG GAS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411970865.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Due to the extremely similar physical and chemical properties of ethylene and ethane, traditional gas separation methods have insufficient energy consumption, long time consumption, and large equipment investment, making it difficult to separate efficiently.

Method used

Using a six-coordinated single-core Ag(I) complex crystal material, C57H55AgBN7O [Ag(BPA-TPA)][BPh4]·C4H8O2 material of C57H55AgBN7O is prepared through coordination reaction. This material has good ethylene selective adsorption properties and can efficiently separate ethylene/ethane mixed gas.

Benefits of technology

It realizes efficient separation of ethylene/ethane mixed gas, the material has good stability and selective adsorption, the production and preparation process is simple, the yield is high, and the controllability is good.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751341A_ABST
    Figure CN119751341A_ABST
Patent Text Reader

Abstract

The invention discloses a hexacoordinated mononuclear Ag(I) complex crystal material, a preparation method, a load and a device, wherein the crystal material has a chemical formula of C 57 H 55 AgBN7O, the molecular structure is [Ag(BPA-TPA)][BPh4]·C4H8O2, and BPA-TPA is 2,6-bis(bis(2-pyridylmethyl)amino)methylpyridine. The crystalline material of the present invention has good purity and ethylene selective adsorption, can effectively separate ethylene / ethane mixed gas, and the production and preparation process of the material is simple, the yield is high, and the controllability is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of chemical engineering and technology, and in particular to a mononuclear Ag(I) complex crystal material suitable for separation of ethylene / ethane, a preparation method, a load and a device. Background Art

[0002] Ethylene (C 2 H 4 ) is one of the world's largest chemical products and is widely used in the manufacture of polymers such as polyethylene, polyvinyl chloride, polystyrene and other organic chemicals. Steam cracking and ethane dehydrogenation are the main methods for producing ethylene. In these production processes, ethane (C 2 H 6 ) impurities. Therefore, separation and purification of ethylene is of great significance in the field of petrochemicals. However, ethylene and ethane are difficult to separate due to their extremely similar physical and chemical properties. Traditional gas separation methods such as traditional cryogenic distillation and solvent absorption often have shortcomings such as high energy consumption, long time consumption, and large equipment investment. In order to reduce the energy consumption required for separation and reduce costs, it is urgent to develop more efficient, energy-saving and environmentally friendly separation technologies. Adsorption separation technology has the advantages of low energy consumption, simple operation and relatively low cost, and is gradually replacing traditional distillation separation technology. The core of adsorption separation technology lies in the selection of adsorbents.

[0003] As a new adsorption separation technology between physical adsorption and chemical adsorption, π-complexation adsorption separation has good industrial application prospects. For a long time, the research hotspots in this field have focused on loading Ag(I) and Cu(I) on suitable carriers to form composite materials to achieve the separation of ethylene and ethane. When Cowan et al. first used two Ag(I) mononuclear complexes to separate ethylene / ethane, they found that their performance exceeded that of many other composite materials. However, to date, there have been few studies on the use of highly coordinated Ag(I) complexes as π-complexing agents for the adsorption and separation of ethylene / ethane, and the results obtained are very scarce.

[0004] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention

[0005] The purpose of the present invention is to provide a hexacoordinated mononuclear Ag(I) complex crystal material, a preparation method, a load and a device, thereby obtaining a high-selectivity ethylene adsorption crystal material with excellent performance, good stability and ethylene selective adsorption, and capable of efficiently separating ethylene / ethane mixed gas. The production and preparation process of the material is simple, the yield is high, and the controllability is good.

[0006] To achieve the above object, the embodiment of the present invention provides a mononuclear Ag(I) complex crystal material, the chemical formula of which is C 57 H 55 NB 7 O, molecular structure is

[0007] [Ag(BPA-TPA)][BPh 4 ]·C 4 H 8 O 2 , BPA-TPA is 2,6-bis(bis(2-pyridylmethyl)amino)methylpyridine.

[0008] In one or more embodiments of the present invention, the crystal material is a triclinic system, the space group is P-1, and satisfies: the unit cell parameters α=91.718(4)°, β=103.639(4)°, γ=91.769(5)°.

[0009] In one or more embodiments of the present invention, the crystalline material is obtained by coordination reaction of 2,6-bis(bis(2-pyridylmethyl)amino)methylpyridine and monovalent silver.

[0010] In one or more embodiments of the present invention, the monovalent silver is provided by a water-soluble silver salt. Preferably, the silver salt is selected from: AgNO 3 and Ag(CH 3 COO).

[0011] In one or more embodiments of the present invention, the method for preparing a mononuclear Ag(I) complex crystal material comprises the following steps: (1) preparing a + (2) The precursor material and the ligand are dissolved in a mixed solvent of acetonitrile and dioxane to carry out a coordination reaction (the reaction time is preferably 1-4h) to obtain the target crystal.

[0012] [Ag(BPA-TPA)][BPh 4 ]·C 4 H 8 O 2 The material is used for selective separation of ethylene / ethane mixed gas.

[0013] In one or more embodiments of the present invention, the preparation of the precursor material in step (1) comprises: 4 The aqueous solution of (Cas:143-66-8) was added to the Ag + ion solution, stir evenly and filter, and vacuum dry the white precipitate.

[0014] In one or more embodiments of the present invention, in step (2), Ag + The molar ratio of the silver salt to the ligand is 1:(1-2). Preferably, in step (2), AgNO 3 The molar ratio of the precursor material to the ligand is 1:(1-2). The ligand is 2,6-bis(bis(2-pyridylmethyl)amino)methylpyridine.

[0015] In one or more embodiments of the present invention, in step (1), for every 1 mmol AgNO 3 The total amount of water used (i.e. NaBPh 4 The aqueous solution and Ag + The total amount of water in the solution containing ions).

[0016] In one or more embodiments of the present invention, in step (1), Ag + With NaBPh 4 The molar ratio of AgNO is: 1:(1-3). Preferably, in step (1), AgNO 3 With NaBPh 4 The molar ratio is: 1:(1-3), that is, for every 1 mmol AgNO in step (1), 3 Corresponding to 1-3mmol NaBPh 4 Dosage.

[0017] In one or more embodiments of the present invention, in step (2), each 1 mmol Ag + This corresponds to a total amount of 10-15 mL of a mixed solution of acetonitrile and dioxane (the volume ratio of acetonitrile to dioxane is 1:(1-10)). 3 This corresponds to a total amount of 10-15 mL of a mixed solution of acetonitrile and dioxane (the volume ratio of acetonitrile to dioxane is 1:(1-10)).

[0018] In one or more embodiments of the present invention, the support includes a carrier and the aforementioned mononuclear Ag(I) complex crystal material attached to the carrier.

[0019] In one or more embodiments of the present invention, the device includes a main body for providing a loading chamber, wherein the loading chamber contains the mononuclear Ag(I) complex crystal material or the loading material as described above. The device here can be a single adsorber, adsorption tower, adsorption tank, etc., or a complete set of equipment equipped with an adsorber or adsorption tank, etc.

[0020] Compared with the prior art, the mononuclear Ag(I) complex crystal material, preparation method, load and device according to the embodiment of the present invention efficiently obtain a high-quality crystal material with good ethylene selective adsorption and the ability to separate ethylene / ethane mixed gas. The production and preparation process of the material is simple, the yield is high and the controllability is good. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 [Ag(BPA-TPA)][BPh 4 ]·C 4 H 8 O 2 The coordination structure diagram of , where N1-N6 refers to nitrogen atoms, Ag1 refers to the coordinated silver (I) atom, O1 and O1A are oxygen atoms in the dioxane, and B1 is [BPh 4 ] boron atom in the ion;

[0022] Figure 2 [Ag(BPA-TPA)][BPh 4 ]·C 4 H 8 O 2 Powder XRD pattern of

[0023] Figure 3 [Ag(BPA-TPA)][BPh 4 ]·C 4 H 8 O 2 The single component adsorption curve of ethylene;

[0024] Figure 4 [Ag(BPA-TPA)][BPh 4 ]·C 4 H 8 O 2 Single component adsorption curve of ethane. DETAILED DESCRIPTION

[0025] The specific implementation modes of the present invention are described in detail below in conjunction with the accompanying drawings, but it should be understood that the protection scope of the present invention is not limited by the specific implementation modes.

[0026] Unless explicitly stated otherwise, throughout the specification and claims, the term “comprise” or variations such as “include” or “comprising”, etc., will be understood to include the stated elements or components but not to exclude other elements or components.

[0027] Including but not limited to the examples shown below, the reactions are all carried out under a protective atmosphere such as nitrogen or argon. The following examples are carried out under a nitrogen atmosphere.

[0028] Example 1

[0029] The preparation process of the crystal material in this embodiment is as follows: AgNO 3 (1 mmol) and sodium tetraphenylborate (1 mmol) were dissolved in 5 mL and 5 mL (total 10 mL) of water respectively. A large amount of white precipitate was produced after mixing. The white solid was filtered and vacuum dried to obtain AgBPh 4 ; 2,6-bis(bis(2-pyridylmethyl)amino)methylpyridine (BPA-TPA) (1 mmol) and AgBPh 4 (1 mmol) was dissolved in 15 mL of a mixed solvent of acetonitrile and dioxane (acetonitrile: dioxane volume ratio = 1:1), heated under reflux for 2 h to obtain a colorless clear solution, which was allowed to stand and evaporate slowly to obtain colorless crystals, which were the Ag(I) complex crystal material.

[0030] The yield of the Ag(I) complex crystal material prepared in this example is 65.2%.

[0031] The characterization of the Ag(I) complex crystal material prepared in this example is as follows:

[0032] (1) Crystal structure determination

[0033] Select a single crystal of appropriate size under a microscope and use a graphite monochromatized molybdenum target Mo Kα on a Bruker SMARTApex IICCD single crystal instrument at room temperature. Test structure. The APEXII program was used to collect data and determine the unit cell. The structural data were normalized and absorption corrected using the SAINT and SADABS programs. The structure was analyzed using the SHELXTL-97 program. All non-hydrogen atomic coordinates were obtained by difference Fourier synthesis, and the atomic coordinates and anisotropic temperature factors were corrected using the full matrix least squares method. All hydrogen atoms were hydrogenated using theory. The crystallographic data are shown in Table 1, and the structure diagram is shown in Figure 1 , the coordination bond lengths and bond angles are shown in Table 2.

[0034] Table 1 Crystallographic data of the complexes

[0035]

[0036] Table 2 Coordination bond lengths of complexes

[0037]

[0038] Figure 1The structural diagram shows that Ag(I) is coordinated with the six N atoms of the organic ligand 2,6-bis(bis(2-pyridylmethyl)amino)methylpyridine (BPA-TPA) to form a distorted pentagonal single pyramid configuration.

[0039] (2) Powder X-ray diffraction determination of phase purity

[0040] The phase purity of the red block crystal product obtained in this example was characterized using a Bruker D8 Advance powder X-ray diffractometer. Figure 2 As shown, the simulation curve is obtained by simulating the single crystal structure data using Mercury software. The results show that the Ag(I) complex crystal material has reliable phase purity, which provides a guarantee for its application in adsorption and separation materials.

[0041] (3) Adsorption performance test

[0042] The adsorption performance of ethylene and ethane of the obtained complex crystal material was studied using IGA-100 gravimetric adsorption instrument. Figure 3 The single component adsorption curve of ethylene in [Ag(BPA-TPA)][BPh 4 ]·C 4 H 8 O 2 It has a certain adsorption capacity for ethylene gas. Figure 4 Display [Ag(BPA-TPA)][BPh 4 ]·C 4 H 8 O 2 It has almost no adsorption capacity for ethane. Therefore, the crystalline material of the present invention has a certain selective adsorption capacity for ethylene, thereby being able to separate ethylene / ethane mixed gas.

[0043] Example 2

[0044] The preparation process of the crystal material in this embodiment is as follows: AgNO 3 (1 mmol) and sodium tetraphenylborate (1.5 mmol) were dissolved in 10 mL and 5 mL (15 mL in total) of water, respectively. A large amount of white precipitate was produced after mixing. The white solid was filtered and vacuum dried to obtain AgBPh 4 2,6-bis(bis(2-pyridylmethyl)amino)methylpyridine (BPA-TPA) (1.2 mmol) and AgBPh 4 (1 mmol) was dissolved in 15 mL of a mixed solvent of acetonitrile and dioxane (acetonitrile: dioxane = 1:1), heated under reflux for 2 h to obtain a colorless clear solution, which was allowed to stand and evaporate slowly to obtain colorless crystals, which were the Ag(I) complex crystal materials.

[0045] The yield of the Ag(I) complex crystal material prepared in this example is 66.1%. The crystal structure of the product is consistent with Figure 1 The crystal structure shown in Table 1, and the purity of the sample in the embodiment meets the application requirements. At the same time, the sample in this embodiment has a certain selective adsorption capacity for ethylene, and almost no adsorption for ethane, which is basically the same as Figure 3-4 The consistency shown.

[0046] Example 3

[0047] The preparation process of the crystal material in this embodiment is as follows: Ag(CH 3 COO) (1 mmol) and sodium tetraphenylborate (1 mmol) were dissolved in 10 mL and 5 mL (15 mL in total) of water, respectively. A large amount of white precipitate was produced after mixing. The white solid was filtered and vacuum dried to obtain AgBPh 4 2,6-bis(bis(2-pyridylmethyl)amino)methylpyridine (BPA-TPA) (1.2 mmol) and AgBPh 4 (1 mmol) was dissolved in 15 mL of a mixed solvent of acetonitrile and dioxane (acetonitrile: dioxane = 1:1), heated under reflux for 2 h to obtain a colorless clear solution, which was allowed to stand and evaporate slowly to obtain colorless crystals, which were the Ag(I) complex crystal materials.

[0048] The yield of the Ag(I) complex crystal material prepared in this example is 59.5%. The crystal structure of the product is consistent with Figure 1 The crystal structure shown in Table 1, and the purity of the sample in the embodiment meets the application requirements. At the same time, the sample in this embodiment has a high selective adsorption capacity for ethylene, and almost no adsorption for ethane, which is basically the same as Figure 3-4 The consistency shown.

[0049] Example 4

[0050] The difference between the crystal preparation process of this embodiment and that of embodiment 1 is that 2,6-bis(bis(2-pyridylmethyl)amino)methylpyridine (BPA-TPA) (2 mmol) and AgBPh 4 (1 mmol) was dissolved in a mixed solvent of acetonitrile and dioxane.

[0051] The yield of the Ag(I) complex crystal material prepared in this example is 63.1%. The crystal structure of the product is consistent with Figure 1 The crystal structure shown in Table 1, and the purity of the sample in the embodiment meets the application requirements. At the same time, the sample in this embodiment has a high selective adsorption capacity for ethylene, and almost no adsorption for ethane, which is basically the same as Figure 3-4 The consistency shown.

[0052] Example 5

[0053] The difference between the crystal preparation process of this embodiment and that of embodiment 1 is that: AgNO 3 (1 mmol) and sodium tetraphenylborate (2 mmol) were dissolved in 5 mL and 5 mL (10 mL in total) of water respectively, and a large amount of white precipitate was generated after mixing.

[0054] The yield of the Ag(I) complex crystal material prepared in this example is 60.4%. The crystal structure of the product is consistent with Figure 1 The crystal structure shown in Table 1, and the purity of the sample in the embodiment meets the application requirements. At the same time, the sample in this embodiment has a high selective adsorption capacity for ethylene, and almost no adsorption for ethane, which is basically the same as Figure 3-4 The consistency shown.

[0055] Example 6

[0056] The difference between the crystal preparation process of this embodiment and that of embodiment 1 is that: AgNO 3 (1 mmol) and sodium tetraphenylborate (3 mmol) were dissolved in 5 mL and 5 mL (10 mL in total) of water respectively, and a large amount of white precipitate was generated after mixing.

[0057] The yield of the Ag(I) complex crystal material prepared in this example is 58.8%. The crystal structure of the product is consistent with Figure 1 The crystal structure shown in Table 1, and the purity of the sample in the embodiment meets the application requirements. At the same time, the sample in this embodiment has a high selective adsorption capacity for ethylene, and almost no adsorption for ethane, which is basically the same as Figure 3-4 The consistency shown.

[0058] Example 7

[0059] The difference between the crystal preparation process of this embodiment and that of embodiment 1 is that the volume ratio of acetonitrile to dioxane is 1:5.

[0060] The yield of the Ag(I) complex crystal material prepared in this example is 59.8%. The crystal structure of the product is consistent with Figure 1 The crystal structure shown in Table 1, and the purity of the sample in the embodiment meets the application requirements. At the same time, the sample in this embodiment has a high selective adsorption capacity for ethylene, and almost no adsorption for ethane, which is basically the same as Figure 3-4 The consistency shown.

[0061] Example 8

[0062] The only difference between the crystal preparation process of this embodiment and that of embodiment 1 is that the volume ratio of acetonitrile to dioxane is 1:10.

[0063] The yield of the Ag(I) complex crystal material prepared in this example is 60.2%. The crystal structure of the product is consistent with Figure 1 The crystal structure shown in Table 1, and the purity of the sample in the embodiment meets the application requirements. At the same time, the sample in this embodiment has a high selective adsorption capacity for ethylene, and almost no adsorption for ethane, which is basically the same as Figure 3-4 The consistency shown.

[0064] Including but not limited to the crystal materials obtained in the above embodiments, all meet Figure 1 In the configuration shown, Ag(I) coordinates with the six N atoms of the organic ligand 2,6-bis(bis(2-pyridylmethyl)amino)methylpyridine (BPA-TPA) to form a distorted pentagonal pyramid configuration. At the same time, like the sample obtained in Example 1, the samples obtained in each example have phase purity and high selective adsorption capacity for ethylene, thereby being able to separate ethylene / ethane mixed gas.

[0065] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is clear that many changes and variations can be made based on the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes. The scope of the present invention is intended to be limited by the claims and their equivalents.

Claims

1. A hexacoordinated mononuclear Ag(I) complex crystal material, the chemical formula of which is C 57 H 55 AgBN7O, molecular formula [Ag(BPA-TPA)][BPh4]·C4H8O2, BPA-TPA is 2,6-bis(bis(2-pyridylmethyl)amino)methylpyridine.

2. The mononuclear Ag(I) complex crystal material according to claim 1, characterized in that: The crystal material is a triclinic system, the space group is P-1, and satisfies the unit cell parameters: α=91.718(4) o ,β=103.639(4) o ,γ=91.769(5) o .

3. The mononuclear Ag(I) complex crystal material according to any one of claims 1 to 2, characterized in that: The crystal material is obtained by coordination reaction of 2,6-bis(bis(2-pyridylmethyl)amino)methylpyridine and monovalent silver.

4. The mononuclear Ag(I) complex crystal material according to claim 3, characterized in that: The monovalent silver is provided by a silver salt soluble in water.

5. A method for preparing a mononuclear Ag(I) complex crystal material, comprising the following steps: (1) Prepare for providing Ag + Precursor materials; (2) The precursor material and the ligand are dissolved in a mixed solvent of acetonitrile and dioxane to carry out coordination reaction to obtain the target crystal.

6. The method for preparing the mononuclear Ag(I) complex crystal material according to claim 5, characterized in that: The preparation of the precursor material in step (1) comprises adding an aqueous solution of NaBPh4 to a mixture containing Ag. + ion solution, stir evenly and filter, and vacuum dry the white precipitate.

7. The method for preparing the mononuclear Ag(I) complex crystal material according to claim 5, characterized in that: In step (1), Ag + The molar ratio with NaBPh4 is: 1:(1-3).

8. The method for preparing the mononuclear Ag(I) complex crystal material according to claim 5, characterized in that: In step (2), Ag + The molar ratio of silver salt to ligand is 1:(1-2).

9. A support, comprising a carrier and the mononuclear Ag(I) complex crystal material according to any one of claims 1 to 4 attached to the carrier.

10. A device comprising a main body for providing a loading chamber, wherein the loading chamber contains the crystal material according to any one of claims 1 to 4 or the load according to claim 7.